RISE: Hutan Simpan Lembah Benum exploration 2021: 31 Mac-1 April, Jerantut Pahang, Malaysia / Dr Mohd Muzamir Mahat - Mahat, Mohd Muzamir (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
Researchers from Universiti Teknologi MARA (UiTM) participated in an exploration to Mukim Ulu Cheka, Jerantut, Pahang.